Comparação entre diferentes testes de campo para a verificação do condicionamento físico de atletas de futsal - Heineck, L. M.; Moro, V. L.; Fuke, K.; Matheus, S. C. (Brazilian Journal of Biomotricity, 2011)
The aim of this study was to evaluate the physical conditioning of indoor soccer players through the Multistage Fitness Test (MSFT) and Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1). 12 professional athletes indoor soccer with a mean age of 21.75 ± 3.82 years, mean height of 175.67 ± 4.81 cm and average fat percentage of 10.22 ± 1.37% participated in this study. The MSFT and Yo-Yo IR1 were used to determine maximum heart rate (HRmax), heart rate recovery (HRrec), total distance, total time and maximum speed. The Student`s paired t test and analysis of variance (ANOVA) for repeated measures completed with Tukey`s post hoc test were used for data analysis. The results showed statistically significant differences in variables HRrec 5 min, total time and maximum speed when comparing the Yo-Yo IR1 with MSFT. Our results suggest that the Yo-Yo IR1 appears to be more appropriate for assessing the physical conditioning of indoor soccer players due to their intermittent characteristics. We emphasize that the HRrec 5 min shown a good indicator of the capacity for physical recovery after maximal exercise.